Integration of Multicultural Islamic Religious Education in Inclusive Learning Practices Based on Local Culture - Nanda Fitri Anisa'; Moch Mahsun; Mokhammad Khosim (Universitas Muhammadiyah Sidoarjo, 2026)
This study aims to analyze structural challenges and inclusive learning practices in the implementation of Islamic Religious Education (PAI) in multicultural schools. SMAN Senduro was chosen as the research location because of its plural characteristics in terms of religion, culture, and ethnicity, as well as the strong influence of local wisdom of the Tengger people who uphold the value of tolerance. This research uses a qualitative approach with observation, in-depth interviews, and documentation. The results of the study show that the learning of Islamic Religious Education (PAI) contributes significantly to the formation of students' moderate attitudes, especially in the aspects of tolerance, respect for differences in beliefs, and the ability to interact harmoniously. Moderation values are not only obtained through learning materials, but also through an inclusive school culture and teacher example. However, the formation of religious moderation is still more influenced by the social environment of the school than by the design of learning that explicitly integrates the pedagogy of moderation. The main challenges include the limitations of contextual learning media, the lack of dialogical pedagogy-based planning, and the lack of optimal integration of local culture in the design of the Islamic Religious Education (PAI) curriculum. This study confirms that the effectiveness of multicultural Islamic Religious Education (PAI) depends on the synergy between Islamic teachings, learning practices, and local wisdom. These findings make an empirical and theoretical contribution to the development of dialogical, contextual, and local culture-based religious learning in strengthening students' religious moderation. Highlights• Students develop tolerance and harmonious interaction through contextual religious learning• School environment and teacher example play dominant roles in shaping moderation• Local traditions are linked with religious values to support contextual understanding KeywordsIslamic Religious Education; Multicultural Education; Religious Moderation; Inclusive Learning; Local Culture